Non linear seismic performance of smart tunnel - Wan Ahmad, Saffuan (2009)
The storm water management and road tunnel (SMART) project in Kuala Lumpur (KL) involves the design and construction of a road and drainage tunnel. A portion of tunnel is designed and constructed for dual purpose; firstly, a double deck road tunnel to serve the increasing volume of traffic in the busiest district of KL city and also to alleviate floods. The tunnel were constructed using several techniques such as bored and cut & cover tunneling. There are also two underground junction boxes to allow vehicle entry and exit from the motorway tunnel and two ventilation shafts. Tunnels as one of the biggest underground structures are well known as the safest structures during earthquakes. In theory, tunnel has the lower rate of damage compared than other surface structures. Even though tunnel are much safer compared than surface structures, this study are important to enhance awareness of seismic hazards for tunnel especially in Malaysia. The existing structural analysis application called SAP 2000 has been used in this study based on the theory of finite element method. The analyses are conducted in linear time history and response spectrum analysis. For checking purposes, the result from finite element analysis will be compared with tunnel design capacity.